Implementasi Pendekatan Behaviorisme Untuk Pembentukan Karakter Melalui Nilai PPKn Dan P5 Di SDN Gondangsari 1 Klaten - Ghozy Alfarisy, Muhammad; Mashfufah, Aynin; Prasetyo, Giri; Agustin, Septiana; Siwi, Dwi Anggraeni (Jurnal Dikdas Bantara, 2025)
This study aims to examine the implementation of Pancasila and Civic Education (PPKn) values and the Pancasila Student Profile (P5) through a behaviorist approach in shaping the character of fifth-grade students at SDN Gondangsari 1 Klaten. A descriptive qualitative method was employed, utilizing observation, interviews, and documentation techniques. The findings reveal that consistent application of positive and negative reinforcement effectively shapes student behavior to become more disciplined, responsible, and active in learning activities. PPKn values and P5 dimensions such as collaboration, honesty, and independence were developed through habituation and direct reinforcement by the teacher. However, implementing this strategy requires flexibility, as not all students respond in the same manner. Therefore, the behaviorist strategy is proven effective when combined with a responsive approach tailored to students' needs. These findings are relevant for teachers, schools, and curriculum developers in fostering character education in elementary schools.